Świat emocji nauczyciela polonisty - Gajak-Toczek, Małgorzata (Acta Universitatis Lodziensis. Folia Linguistica, 2007)
The teacher, who is aware of her/his role, attains competences for recognizing her/his states of flutters. She/he must control it, because it can include in the process of forming pupil’s opinions. The author of this article is trying to show importance of emotions in didactics.